Kesahan dan kebolehpercayaan intervensi modul kaunseling rasional emosi tingkah laku - Alwi, Norhanim; Shaari, Azemi (UUM Press, 2017)
This study was conducted to understand the counseling intervention module of Rational Emotive Behavior Theory (REBTM) and to apply the content validity’s process of the draft before REBTM module can be used in the actual study. In this study, REBTM module will be used for the treatment of negative social morality behavior among secondary school’s student. REBTM module is based on ABC system founded by pioneer REBT theory, Albert Ellis. A total of six experts in the field of counseling and counselors trained in this theory were appointed as expert evaluators. Meanwhile, the result of realibility test is Alpha Cronbach .92. The use of the module is expecting to reduce negative behavior among adolescents and to be use as a guidance and reference by all parties in order to help address the problem of negative social morality behavior.